Double-layer gel patch for diabetic wound and preparation method of double-layer gel patch
Through the design of double -layer gel stickers, the lower layer of gels uses photosidomy therapy to achieve antibacterial. The upper layer of gels can achieve anti -inflammatory inflammation through anti -inflammatory drugs. Long -acting antibacterial and anti -inflammatory effect.
Patent Information
- Application Number
- CN202411466192.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-21
AI Technical Summary
Diabetic wounds are slow due to factors such as hyperglycemia, lipid metabolism disorders and insulin resistance, and often have excessive inflammatory reactions and bacterial infections. The existing gel dressings are insufficient mechanical strength, which is easy to lose and can easily cause secondary damage when changing the dressing. .
It uses a double-layer gel patch. The lower gel contains antibacterial agents and is sterilized through photothermal therapy. The upper gel contains anti-inflammatory drugs. It uses materials such as methacrylated gelatin and oxidized hyaluronic acid to form a product with high mechanical strength and Absorbable gel achieves first antibacterial and then anti-inflammatory therapeutic effects.
Accelerate the healing process of the wound of diabetes, improve the mechanical strength and adhesion of the wound, reduce damage during drug replacement, achieve long -active antibiotics and antibacterial effects, and improve the compliance and healing rate of patients.
Smart Images

Figure CN119345160A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medicine, and particularly relates to a double-layer gel patch for diabetic wounds and a preparation method thereof. Background Art
[0002] Diabetic wounds are one of the most common complications of diabetes. They are chronic, difficult-to-heal wounds caused by diabetic peripheral neuropathy, vascular disease, and local tissue infection. Extensive sensory nerve lesions in the patient's skin reduce or lose basic "feelings" and "pain," leading to insensitivity or even unconsciousness of the nervous system to the wound, thereby increasing the risk of ulcers and even amputation. The healing process of a normal wound usually includes four stages: hemostasis, inflammation, proliferation, and remodeling. However, the normal healing process of diabetic wounds is hindered by factors such as a hyperglycemic environment, lipid metabolism disorders, and insulin resistance. Diabetic wounds often show excessive inflammatory responses, which prolongs the time required for the wound to transition from the inflammatory stage to the tissue proliferation stage, causing the wound to be in a chronic inflammatory state for a long time, with continuous tissue damage and even difficulty in wound healing. At the same time, the hyperglycemic environment makes it easier for bacteria to colonize the wound, thereby causing persistent infection of the wound.
[0003] At present, conventional treatments for diabetic wounds include mechanical debridement, local antibiotic treatment, hyperbaric oxygen therapy, and wound dressings. Mechanical debridement is a key link in wound closure and reducing the probability of amputation, but wound debridement is usually not thorough and can easily lead to recurrence, so it is usually combined with drug treatment. Local topical antibiotics are usually only suitable for patients with mild symptoms. Hyperbaric oxygen therapy is expensive and clinical research is limited, making it difficult to evaluate its actual efficacy. Hydrogel dressings have a unique three-dimensional mesh porous structure and stronger water absorption properties. They can keep the wound in a moist environment for a long time, while providing a suitable environment for cell attachment, survival and proliferation. They are ideal dressings for diabetic wounds. However, most existing gel dressings have insufficient mechanical strength and are easy to leak from the wound. When the backing is bandaged and the dressing is changed, it is usually easy to cause secondary damage and infection to the wound due to mechanical tearing, which greatly reduces the patient's compliance. Therefore, it is of great clinical significance to construct a gel dressing with strong mechanical strength and absorbability to cover and protect the open wound for a long time, while avoiding tearing during dressing changes, for the treatment of diabetic wounds.
[0004] At the same time, based on the complexity of the diabetic microenvironment, namely the high sugar environment, persistent bacterial infection and retention in the inflammatory stage, most of the gel treatments currently used only treat a single wound environmental factor, and the singleness of the treatment usually leads to poor wound healing efficacy or a risk of recurrence. Therefore, the present invention is designed to adopt a double-layer gel multi-stage combined treatment and a staged sequential treatment strategy. The lower layer first releases the antibacterial agent, uses photothermal therapy for sterilization, and then releases the anti-inflammatory drug in the upper layer of gel to achieve the therapeutic effect of first antibacterial and then anti-inflammatory, which is conducive to accelerating the healing process of diabetic wounds. Summary of the invention
[0005] One of the purposes of the present invention is to provide a double-layer gel patch, which is composed of an upper gel layer and a lower gel layer, and the lower gel layer is applied to the skin surface when in use; The upper gel layer is made of methacryloyl gelatin, oxidized hyaluronic acid, a photoinitiator and an anti-inflammatory drug, the mass ratio of methacryloyl gelatin to oxidized hyaluronic acid is 20-30:10-20, the mass percentage of the photoinitiator is 0.2wt.%, and the concentration of the anti-inflammatory drug is 1mg / mL; The lower gel layer is made of 3-carboxyphenylboronic acid grafted gelatin, dihydrocaffeic acid grafted ε-polylysine and an antibacterial agent, the mass ratio of 3-carboxyphenylboronic acid grafted gelatin and dihydrocaffeic acid grafted ε-polylysine is 5:1, and the concentration of the antibacterial agent is 100 μg / mL.
[0006] Furthermore, the thickness of the upper gel layer and the lower gel layer are the same, and the area ratio is 5:1.
[0007] Furthermore, the photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and the anti-inflammatory drug is nimesulide.
[0008] Furthermore, the antibacterial agent is copper sulfide nanoparticles.
[0009] In an embodiment of the present invention, the mass ratio of methacryloyl gelatin to oxidized hyaluronic acid is preferably 25-30:10-15, more preferably 25:15.
[0010] The second object of the present invention is to provide a method for preparing the above-mentioned double-layer gel patch, comprising the following steps: Step 1, dissolving methacrylated gelatin and oxidized hyaluronic acid in water respectively, then mixing the two, adding a photoinitiator and an anti-inflammatory drug to the mixture to obtain an upper gel precursor solution; Step 2, injecting the upper gel precursor solution into mold A, cross-linking and curing under ultraviolet conditions to obtain an upper gel layer; Step 3, dissolving 3-carboxyphenylboronic acid grafted gelatin in water, and then adding an antibacterial agent; Step 4, dissolving the dihydrocaffeic acid grafted ε-polylysine in water, adjusting the solution pH to 9, adding it to the mixed solution of step 3, and injecting it into mold B after gelation to obtain a lower gel layer; Step 5, combining the upper gel layer and the lower gel layer for self-healing, and allowing them to stand for cross-linking to obtain the double-layer gel patch.
[0011] Furthermore, in step 2, the ultraviolet condition is 405 nm.
[0012] Furthermore, the static cross-linking condition in step 5 is 4°C.
[0013] The third object of the present invention is to provide the use of the double-layer gel patch in the preparation of external medicines for treating diabetic wounds.
[0014] The present invention selects dihydrocaffeic acid grafted ε-polylysine containing a catechol group, and crosslinks with 3-carboxyphenylboronic acid grafted gelatin to form a lower gel by forming a phenylboronic acid ester bond. The high sugar microenvironment of the diabetic wound causes the phenylboronic acid ester bond to break, and the lower gel responds quickly to liquefaction, and the copper sulfide carried is precipitated on the wound surface, and then photothermal antibacterial is produced by 808 nm near-infrared light, and the ε-polylysine in the gel can continue to inhibit bacteria on the wound surface; the methacrylylated gelatin in the upper gel is cross-linked into a gel under ultraviolet light with a wavelength of 405 nm, and the formed gel has high mechanical strength, elasticity and adhesion, which can cover and fit the wound to prevent secondary infection, and can avoid mechanical tearing and secondary damage after the end of medication, and at the same time, anti-inflammatory drugs are loaded as a gel reservoir to exert a long-term anti-inflammatory effect. The double-layer gel of the present invention has both high mechanical strength and absorbability, and can realize a sequential treatment strategy of first antibacterial and then anti-inflammatory. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a macroscopic morphology of the double-layer gel patch prepared in Example 1.
[0016] Figure 2 Graph showing the maximum compressive stress of the double-layer gel patch prepared in Examples 1-3.
[0017] Figure 3 Graph showing the adhesion strength of the double-layer gel patch prepared in Examples 1-3.
[0018] Figure 4 Graph showing the percentage of drug release from the double-layer gel patch prepared in Examples 1-3.
[0019] Figure 5 This is a graph showing the glucose-responsive morphological changes of the double-layer gel patch prepared in Example 1.
[0020] Figure 6 This is a graph showing the temperature change over time of the copper sulfide solution and the lower gel under 808 nm near-infrared light.
[0021] Figure 7 This is the residual rate diagram of the gel degradation process.
[0022] Figure 8 The figure shows the inhibitory effect of the gel on Escherichia coli and Staphylococcus aureus, where A is the antibacterial effect diagram of the plate coating, B is the survival rate of Escherichia coli, and C is the survival rate of Staphylococcus aureus.
[0023] Fig. 9 This is the healing effect of infected wounds in 14-day diabetic rats. DETAILED DESCRIPTION
[0024] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0025] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0026] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0027] In the present invention, the methacryloyl gelatin, oxidized hyaluronic acid, 3-carboxyphenylboronic acid grafted gelatin, dihydrocaffeic acid grafted ε-polylysine and copper sulfide nanoparticles can be prepared by methods reported in existing literature. In the following examples, they are prepared by the following method.
[0028] Preparation of methacrylated gelatin: Place 10 g of gelatin in 200 mL of PBS and stir to dissolve at 50°C. Slowly add 6 mL of methacrylic anhydride to the gelatin solution and stir vigorously at 50°C for 2 hours. Preheat 50 mL of PBS to 50°C, add it to the concentrated solution for dilution, and stir at 50°C for 10 min. Then dialyze at 40°C for 7 days using a 12-14 kDa dialysis bag. After dialysis, add 100 mL of preheated ultrapure water to the solution for dilution, stir at 40°C for 15 min, quickly transfer to a tray, and freeze-dry for 2 days to obtain a white porous foam product.
[0029] Preparation of oxidized hyaluronic acid: Weigh 2 g of hyaluronic acid and dissolve it in 200 mL of deionized water, stirring to completely dissolve it. Dissolve 1.072 g of sodium periodate in 10 mL of deionized water, then add dropwise to the above hyaluronic acid solution, and stir in an ice bath in the dark for 24 h. Then add 1 mL of ethylene glycol to terminate the reaction for 1 h. After the reaction, transfer the reaction solution into an 8k-14kD dialysis bag and dialyze for three days to obtain the product.
[0030] Preparation of 3-carboxyphenylboronic acid grafted gelatin: 4 g gelatin was dissolved in 100 mL pure water at 40°C. At the same time, 1 g of 3-carboxyphenylboronic acid was dissolved in 20 mL methanol, 1 g of EDC and 575 mg of NHS were dissolved in 20 mL water, mixed, and activated in an ice bath for 30 min. Then, the activated 3-carboxyphenylboronic acid solution was added dropwise to the gelatin aqueous solution and reacted in a 37°C water bath for 48 h. The product was dialyzed in deionized water at pH 7.4 for 3 days using a dialysis bag and freeze-dried to obtain a white solid.
[0031] Preparation of dihydrocaffeic acid grafted ε-polylysine: Dissolve 1.2 g ε-polylysine and 167 mg NHS in 40 mL deionized water. Then dissolve 427 mg dihydrocaffeic acid in 40 mL acetonitrile, add the acetonitrile solution of dihydrocaffeic acid to the ε-polylysine aqueous solution and stir evenly. Weigh 500 mg EDC and dissolve it in 20 mL deionized water, add it dropwise to the above solution, react at room temperature in the dark for 24 h, then put the resulting solution into a 1 kDa dialysis bag for 3 days, and finally freeze-dry it.
[0032] Preparation of copper sulfide nanoparticles: 2.4 g PVP-K30 was dissolved in 250 mL water, stirred until dissolved, 1 mL 0.5 mol / L copper chloride solution was added dropwise, stirred vigorously at room temperature for 5 min, 250 mL sodium hydroxide (pH=9) was added, stirred evenly, 80 μL 80% hydrazine hydrate was added dropwise, stirred vigorously at room temperature for 10 min, and finally 4 mL of 160 mg / mL sodium sulfide solution was added, heated in a water bath at 60°C, and stirred vigorously for 2 h. After centrifugation at 10,000 rpm for 10 min, the mixture was washed three times with ultrapure water until neutral, and freeze-dried for 2 days. Example 1
[0033] This embodiment is a method for preparing a double-layer gel patch consisting of a blank upper gel layer and a blank lower gel layer, and the specific steps are as follows: Step 1, take 1 g of methacryloyl gelatin (GelMA) and dissolve it in 2 mL of deionized water, heat and stir at 40°C until dissolved; take 600 mg of oxidized hyaluronic acid (OHA) and dissolve it in 2 mL of deionized water, stir until completely dissolved, and stir and mix the two solutions evenly; take 8 mg of phenyl-2,4,6-trimethylbenzoyl lithium phosphite, add it to the above mixed solution and stir evenly to prepare a blank upper gel precursor solution; Step 2, 1 mL of the blank upper layer gel precursor solution was injected into a 20 mm * 20 mm * 2 mm square polydimethylsiloxane mold, and photocrosslinked under 405 nm ultraviolet light for 10 min to form a blank upper layer hydrogel (UPgel); Step 3, take 200 mg of 3-carboxyphenylboronic acid grafted gelatin and dissolve it in 3 mL of deionized water, heat and stir at 37°C until dissolved; Step 4, take 40 mg of dihydrocaffeic acid grafted ε-polylysine and dissolve it in 1 mL of deionized water, stir until completely dissolved, adjust the pH to 9 with sodium hydroxide, add it dropwise into the solution of step 3 under stirring to obtain a gel precursor solution, and form a blank lower layer gel (BT gel) within 1 minute; inject the blank lower layer gel into a circular polydimethylsiloxane mold with a diameter of 10 mm and a thickness of 2 mm, and continue crosslinking at 4°C for 10 minutes; Step 5: Combine the blank upper gel and the blank lower gel for self-healing, cross-link at 4°C for 20 min, and demold to obtain a blank double-layer gel (UP / BT gel).
[0034] like Figure 1 As shown, the appearance of the double-layer gel is a square upper layer and a round lower layer. The upper layer has a larger area and is conducive to completely covering the wound surface. The lower layer directly contacts the wound surface to exert its medicinal effect, and the cross-linking effect between the two layers is good. Example 2
[0035] The difference between this embodiment and embodiment 1 is that the amount of methacryloyl gelatin in the upper gel precursor solution is 20% by volume, the amount of oxidized hyaluronic acid is 20% by volume, and the rest is the same as embodiment 1. Example 3
[0036] The difference between this embodiment and embodiment 1 is that the amount of methacryloyl gelatin in the upper gel precursor solution is 30% by volume, the amount of oxidized hyaluronic acid is 10% by volume, and the rest is the same as embodiment 1. Example 4
[0037] The difference between this embodiment and embodiment 1 is that the amount of methacryloyl gelatin in the upper gel precursor solution is 30% by volume, the amount of oxidized hyaluronic acid is 10% by volume, and the rest is the same as embodiment 1. Example 5
[0038] The difference between this embodiment and embodiment 1 is that the amount of 3-carboxyphenylboronic acid grafted gelatin in the lower layer gel is 10% by mass volume, the amount of dihydrocaffeic acid grafted ε-polylysine is 2% by mass volume, and the rest is the same as embodiment 1.
[0039] During the preparation process, it was observed that the glucose response time of the lower gel formed at this ratio was relatively long, which was (19.49±0.61) min. Example 6
[0040] The difference between this embodiment and embodiment 1 is that the gel precursor solution in step 2 contains 1 mg / mL nimesulide solution, and the nimesulide-loaded upper gel and blank lower gel (NIM@UP / BT gel) are prepared, and the rest is the same as embodiment 1. Example 7
[0041] The difference between this embodiment and embodiment 1 is that the gel precursor solution in step 4 contains 100 μg / mL ultrasonically dispersed copper sulfide (CuS) solution, and a blank upper gel and a copper sulfide-loaded lower gel (UP / CuS@BT gel) are prepared, and the rest is the same as embodiment 1. Example 8
[0042] The difference between this embodiment and embodiment 1 is that the gel precursor solution in step 2 contains 1 mg / mL nimesulide solution, and the gel precursor solution in step 4 contains 100 μg / mL ultrasonically dispersed copper sulfide (CuS) solution, and an upper gel containing nimesulide and a lower gel containing copper sulfide (NIM@UP / CuS@BT gel) are prepared, and the rest is the same as embodiment 1.
[0043] The gel obtained in the above example is measured below: 1. Determination of Gel Mechanical Properties The compression force of the gel patches of Examples 1 to 3 was tested using a universal mechanical testing machine, and the mechanical strength of the prepared gels was analyzed.
[0044] The experimental results are as follows Figure 2 As shown, it can be seen that the maximum compressive stress of the gel prepared in Example 1 is the highest, indicating that its mechanical strength is optimal and can better meet the design requirements.
[0045] 2. Gel Adhesion Test The adhesion of the gel patches of Examples 1 to 3 was measured by shear tensile test, and the adhesion strength was calculated by the formula "σ=F / (Lb)" (wherein σ represents tensile shear strength, MPa; F represents breaking load, N; L represents bonding surface length, mm; b represents bonding surface width, mm).
[0046] The experimental results are as follows Figure 3 As shown, the adhesion strength increases with the increase of the content of methacryloyl gelatin, which depends on the bioadhesiveness of methacryloyl gelatin itself. The gel prepared in Example 3 has the strongest adhesion, while the gel prepared in Example 1 has a medium adhesion.
[0047] 3. Determination of drug release properties of gel The in vitro drug release behavior of the gel patch of Examples 1 to 3 was investigated by using a membraneless dissolution model and pH 7.4 PBS solution as the release medium. The upper gel precursor solution containing 1 mg / mL nimesulide was prepared according to the ratio described in Examples 1 to 3, and the demolded gel was placed in a beaker containing 50 mL pH 7.4 PBS solution, and the beaker was placed in a 37 ºC constant temperature shaker and shaken at 100 rpm. At the predetermined time points (0.25 h, 0.5 h, 1 h, 1.5 h, 2 h, 3 h, 4 h, 6 h, 8 h, 10 h, 12 h, 24 h), 1 mL of release medium was taken out, and 1 mL of release medium was added at the same time. After the collected solutions at each time point were centrifuged at 10000 rpm for 10 min, the supernatant was taken and the nimesulide concentration was determined by ultraviolet spectrophotometry, and the cumulative release percentage of nimesulide at each time point was calculated.
[0048] The experimental results are as follows Figure 4 As shown in the figure, the cumulative release of nimesulide decreases with the increase of the content of methacryloyl gelatin. This may be because the increase of methacryloyl gelatin leads to an increase in the cross-linking density of the gel, which leads to a decrease in the dense pore size of the three-dimensional network of the gel, resulting in a decrease in the cumulative release of the drug. The release rate and the cumulative release amount show an opposite trend. The gel prepared in Example 1 has a sustained release effect within 4 hours before release, and the release rate is medium. In Example 2, the gel releases nimesulide faster, and the gel skeleton is almost dissolved after release, which is not conducive to the sustained release of the drug; in Example 3, the gel releases slowly, but its cumulative release rate is only 47%. Considering the mechanical strength, adhesion and drug release performance, the preferred ratio of methacryloyl gelatin to oxidized hyaluronic acid is 25:15.
[0049] 4. Glucose response performance measurement The gel prepared in Example 8 was placed on a clean glass slide with the lower layer of gel facing upward. A 9 mg / mL glucose solution was dripped onto the surface of the gel, and the liquefaction time of the lower layer of gel was recorded.
[0050] The experimental results are as follows Figure 5 As shown in the figure, the lower layer of gel liquefied after 12 minutes under the action of glucose solution, and its morphology changed from solid to liquid, while the upper layer of gel always maintained its intact morphology, indicating that the lower layer of the double-layer gel patch can quickly respond to the high-sugar environment of the diabetic wound, liquefy to fill the wound shape and release copper sulfide nanoparticles, which is beneficial for subsequent infrared irradiation and photothermal sterilization; while the upper layer stably covers the wound to prevent the liquefaction and loss of the lower layer of gel.
[0051] 5. Determination of photothermal properties of gel The lower gel (CuS@BT gel) prepared in Example 8 was placed in a 1.5 mL ep tube, and a deionized water group (DI Water), a 100 μg / mL CuS solution, and a blank lower gel (BT gel) prepared in step 4 of Example 1 were set as control groups. The sample was irradiated with 808 nm near-infrared light for 10 min, during which the temperature was recorded every 30 s using an infrared thermal imager to observe the change in sample temperature over time.
[0052] like Figure 6 As shown in the figure, CuS@BT gel has good photothermal performance. After 10 minutes of 808 nm near-infrared light irradiation, the temperature can reach 55°C, which is beneficial to wound antibacterial; the temperature of the CuS solution reaches 50.7°C after 10 minutes, which has excellent photothermal conversion performance. The temperature of BT gel also increased compared with the control group under near-infrared light irradiation, which may be due to the catechol structure in dihydrocaffeic acid has the ability to capture free radicals, giving the gel itself certain photothermal conversion performance.
[0053] 6. Gel degradation performance determination The in vitro degradation performance of the upper hydrogel in step 2 and the lower gel in step 4 in Example 1 was investigated by weight method. The prepared gel was weighed and recorded as m1, then immersed in a PBS solution and placed in a 37°C incubator. On days 1, 2, 4, 6, 8, 10, 16, and 20, the hydrogel was taken out of the PBS solution and weighed as m2. The residual rate percentage during the degradation of the hydrogel was calculated as: residual rate = m2 / m1×100%.
[0054] The residual rate results are as follows Figure 7 As shown in the figure, the upper layer of gel swelled in the initial stage and degraded slowly, and was completely degraded after 20 days. The lower layer of gel degraded faster and was almost completely degraded on the 10th day. It is speculated that this may be because the mechanical strength of the lower layer of gel is weaker than that of the upper layer of gel, making it easier to degrade. The experimental results show that both the upper and lower layers of the gel have good biodegradability and can be degraded and absorbed by the wound to avoid damage during dressing changes.
[0055] 7. In vitro antibacterial properties of gel Six experimental groups were set up: PBS group, 3-carboxyl grafted phenylboronic acid group (PBA), blank lower gel group (BT gel) obtained in step 4 of Example 1, infrared light irradiated CuS solution group (CuS / NIR+), non-infrared light irradiated CuS solution group (CuS / NIR-), and lower gel group (CuS@BT gel) obtained in Example 8.
[0056] Escherichia coli or Staphylococcus aureus were incubated overnight in a shaker at 220 rpm and 37°C. Bacteria in the logarithmic growth phase were taken and the bacterial suspension was diluted to 10 with LB medium. 6 CFU / mL; 5% PBA solution, 100 μg / mL CuS solution, BT gel and CuS@BT gel were prepared in advance, and 500 μL of the prepared samples were added to 1.5 mL ep tubes, and then 500 μL of the diluted bacterial solution was added. After irradiation with 808 nm near-infrared light for 10 min, 100 μL of the supernatant bacterial solution was taken from each group, diluted 100 times and then spread on agar plates. The spread plates were incubated in a 37°C incubator overnight, and the number of colonies on the plates was observed.
[0057] The experimental results are as follows Figure 8 As shown, Figure A shows the growth of Escherichia coli and Staphylococcus aureus on agar plates. Compared with the control group PBS, the CuS / NIR+ group and the BT gel group both showed good antibacterial effects, which came from the photothermal effect of CuS and the cationic antibacterial effect of ε-polylysine in BT gel. Figures B and C show the survival rates of Escherichia coli and Staphylococcus aureus, respectively. It can be seen that CuS@BT gel has the strongest antibacterial effect, indicating that the antibacterial effect of the gel obtained in Example 1 and the photothermal properties imparted by CuS act together on wound pathogens to achieve antibacterial synergy.
[0058] 8. In vivo wound healing effect Establishment of type 2 diabetes and infected wound model in SD rats: 30 SD rats were adaptively fed with ordinary feed for 1 week, and then each cage of rats was fed with high-sugar and high-fat feed for 4 weeks. SD rats were intraperitoneally injected with 1% streptozotocin at a dose of 35 mg / kg, and high-sugar and high-fat feeding was continued during the period. If the fasting blood glucose value of the rats reached 13.5 mmol / L 7 days after injection, and accompanied by diabetic symptoms such as polydipsia, polyphagia, and loose and yellow hair, the diabetic rat model was considered successful. Diabetic rats that were successfully modeled according to the above standards were selected and anesthetized with 1% sodium pentobarbital solution injected intraperitoneally. After anesthesia, the rats were fixed on the operating table, all the hair on the back was removed, and a wound with a diameter of 10 mm was made. Subsequently, 50 μL of Staphylococcus aureus suspension (10 8 CFU / mL), forming a diabetic rat wound infection model.
[0059] The rats with successful modeling were divided into 5 groups, namely PBS group, blank double-layer gel group (UP / BT gel), blank upper gel and copper sulfide-loaded lower gel (UP / CuS@BT gel), nimesulide-loaded upper gel and blank lower gel (NIM@UP / BT gel), and gel (NIM@UP / CuS@BT gel) prepared in Example 8. Wound images of diabetic rats were collected on days 0, 3, 7, and 14 after administration.
[0060] Wound healing effects such as Fig. 9 As shown, compared with the control group, each group of gels effectively promoted wound healing, among which the double-layer gel NIM@UP / CuS@BT gel group loaded with nimesulide and copper sulfide had the best wound healing effect, and the difference in healing effect could be clearly observed on the 7th day. Comparing the UP / BT gel group with the UP / CuS@BT gel group, it can be seen that the UP / CuS@BT gel group has a better healing effect, indicating that the antibacterial effect of copper sulfide is beneficial to promote the development of wound healing; comparing the UP / CuS@BT gel group with the NIM@UP / CuS@BT gel group, it can be seen that the healing rate of the NIM@UP / CuS@BT gel group is faster, indicating that the anti-inflammatory effect of nimesulide can effectively promote wound healing. The above results show that the double-layer gel patch of the present invention has potential application value in the field of diabetic wound treatment.
Claims
1. A double-layer gel patch, characterized in that: It consists of an upper gel layer and a lower gel layer. When in use, the lower gel layer is applied to the skin surface; The upper gel layer is made of methacryloyl gelatin, oxidized hyaluronic acid, a photoinitiator and an anti-inflammatory drug, the mass ratio of methacryloyl gelatin to oxidized hyaluronic acid is 20-30:10-20, the mass percentage of the photoinitiator is 0.2wt.%, and the concentration of the anti-inflammatory drug is 1mg / mL; The lower gel layer is made of 3-carboxyphenylboronic acid grafted gelatin, dihydrocaffeic acid grafted ε-polylysine and an antibacterial agent, the mass ratio of 3-carboxyphenylboronic acid grafted gelatin and dihydrocaffeic acid grafted ε-polylysine is 5:1, and the concentration of the antibacterial agent is 100 μg / mL.
2. The double-layer gel patch according to claim 1, characterized in that: The upper gel layer and the lower gel layer have the same thickness, and the area ratio is 5:
1.
3. The double-layer gel patch according to claim 1, characterized in that: The photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphite, and the anti-inflammatory drug is nimesulide.
4. The double-layer gel patch according to claim 3, characterized in that: The antibacterial agent is copper sulfide nanoparticles.
5. The method for preparing the double-layer gel patch according to claim 1, characterized in that: The following steps are involved: Step 1, dissolving methacrylated gelatin and oxidized hyaluronic acid in water respectively, then mixing the two, adding a photoinitiator and an anti-inflammatory drug to the mixture to obtain an upper gel precursor solution; Step 2, injecting the upper gel precursor solution into mold A, cross-linking and curing under ultraviolet conditions to obtain an upper gel layer; Step 3, dissolving 3-carboxyphenylboronic acid grafted gelatin in water, and then adding an antibacterial agent; Step 4, dissolving the dihydrocaffeic acid grafted ε-polylysine in water, adjusting the solution pH to 9, adding it to the mixed solution of step 3, and injecting it into mold B after gelation to obtain a lower gel layer; Step 5, combining the upper gel layer and the lower gel layer for self-healing, and allowing them to stand for cross-linking to obtain the double-layer gel patch.
6. The preparation method according to claim 6, characterized in that: The UV condition in step 2 is 405 nm.
7. The preparation method according to claim 6, characterized in that: The static cross-linking condition in step 5 is 4°C.
8. Use of the double-layer gel patch according to claim 1 in preparing a topical medicine for treating diabetic wounds.
Citation Information
Patent Citations
Double-layer hydrogel material as well as preparation method and application thereof
CN114984322A
Double-layer gel system carrying mesenchymal stem cell spheres as well as preparation method and application of double-layer gel system
CN115414319A
Polydopamine mesoporous nanoparticle cross-linked sulfhydrylated hyaluronic acid hydrogel as well as preparation method and application thereof
CN117820858A
Oxygen-releasing and anti-inflammatory double-layer hydrogel as well as preparation method and application thereof
CN118286503A
Bionic double-layer multifunctional hydrogel repair patch
CN219721358U
Cited By
Spatial separation double-layer hydrogel as well as preparation method and application thereof
CN120227462A
A spatially separated double-layer hydrogel and its preparation method and application
CN120227462B